Phytoremediation potential of Nerium oleander and Salix alba for heavy metal removal in rock-amended soils: a natural and cost-effective approach - Ibrahim, Naira; Smith, Zavier; Zhang, Huimin; Roy, Subrata Chandra; Islam, Saiful M.; Arora, Bhavna (Frontiers in Earth Science, 2025)
Enhanced weathering (EW) through the application of ground rock is a competitive carbon removal strategy. Adoption of this technology at a meaningful scale requires a systematic assessment of its long-term feasibility, especially with regard to soil quality from the application of rock amendments that contain varying levels of heavy metal (loid)s (HM) such as Cu, Ni, Cr, Co, and Pb. The potential accumulation of these metal (loid)s could be an unintended consequence of repeated large-scale EW applications, necessitating careful evaluation for use in croplands. This study explores the idea of using phytoremediation as a natural, low-cost means of remediating rock-amended soils. Specifically, we examined the ability of Nerium oleander and Salix alba species to remove HM from rock-amended soils in their tissues (i.e., leaves, stems, and roots). In this study, the relative abundance of HM accumulation in hyperaccumulator plants followed the order: Si > Rb > Cu > Sn > Cr > Cd > Pb > Ni > Mo > Co > As > Sb > Se > Cs. Our results indicate that HM accumulation in soils treated with rock were significantly below permissible limits set by the Environmental Protection Agency (EPA). Further, in reasonable amounts, some of these HM serve as essential micronutrients required by plants. In fact, we found increased growth and higher biomass for both plants under rock application than without. We further found a significant uptake of most HM in rock-amended soils planted with S. alba. Comparatively, uptake of certain HM like Ni, Mo, Cs, Pb and Cu was relatively higher in the roots of N. oleander. In contrast to N. oleander, S. alba accumulated higher levels of HM in its stems and leaves than in its roots. Interestingly, 31–35% weathering of metabasalt (applied rock) was observed across plant types over a 5-month period. Overall, we conclude that S. alba has a greater potential for phytoremediation in rock-amended soils, although both plants may be useful in remediating soils with varying levels and types of contamination.